Screening preemergence herbicides for weed control in cassava. (17th October 2020) - Ekeleme, Friday; Dixon, Alfred; Atser, Godwin; Hauser, Stefan; Chikoye, David; Olorunmaiye, Patience M.; Olojede, Adeyemi; Korie, Sam; Weller, Stephen
Abstract: Weed competition severely constrains cassava root yield in sub-Saharan Africa; thus, good weed control measures, including the use of herbicides, are increasingly important. Herbicide trials were conducted at five locations across eastern, western, and north-central Nigeria over two cropping seasons (2014 and 2015). Nineteen premixed PRE herbicides applied at different rates were evaluated for efficacy on weeds and selectivity on cassava. Manual hoe-weeding at 4, 8, and 12 wk after planting (WAP) and two S -metolachlor + atrazine treatments commonly used by cassava growers were included for comparison. Six of the 19 PRE herbicide treatments (indaziflam + isoxaflutole, indaziflam + metribuzin, flumioxazin + pyroxasulfone, isoxaflutole, acetochlor + atrazine + terbuthylazine, and terbuthylazine + S -metolachlor) consistently provided 80% to 98% broadleaf and grass weed control up to 8 wk after treatment. Overall, PRE herbicide treatments and cassava yield were significantly positively correlated. Herbicide treatments terbuthylazine + S -metolachlor, flumioxazin + pyroxasulfone, diflufenican + flufenacet + flurtamone (respectively, 60 + 60 + 60, 120 + 120 + 120, 90 + 360 + 120, and 135 + 360 + 180 g ha −1 ), acetochlor + atrazine + terbuthylazine (875 + 875 + 875 g ha −1 ), S -metolachlor + atrazine (870 + 1, 110 g ha −1 ), oxyfluorfen (240 g ha −1 ), indaziflam + isoxaflutole (75 + 225 g ha −1 ), indaziflam + metribuzin (75 + 960 g ha −1 ), and aclonifen + isoxaflutole (500 + 75 g ha −1 ) contributed to yields exceeding twice the Nigerian national average of 8.76 tonnes ha −1 . These treatments had root yields of 1.4 to 2 times higher than plots that had been hoe-weeded three times. There were some adverse herbicide treatment effects such as delayed cassava sprouting and temporary leaf bleaching observed in indaziflam and diflufenican + flufenacet + flurtamone treatments, whereas sulfentrazone caused prolonged leaf crinkling. The PRE applications alone at rates safe for cassava did not provide adequate season-long weed control; supplemental POST weed control is needed about 10 WAP for satisfactory season-long control.